2010
DOI: 10.1007/s10571-010-9567-z
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Adrenergic Function: HIF1α, a Potential Regulatory Switch

Abstract: Stress elicits adrenal epinephrine and cortisol release into the bloodstream to initiate physiological and behavioral responses to counter and overcome stress, the classic "fight or flight" response (Cannon and De La Paz, Am J Physiol 28:64-70, 1911). Stress and the stress hormone epinephrine also contribute to the pathophysiology of illness, e.g., behavioral disorders, cardiovascular disease, and immune dysfunction. Epinephrine itself is regulated by stress through its biosynthesis by phenylethanolamine N-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
(57 reference statements)
3
16
0
Order By: Relevance
“…S-adenosylmethionine is the methyl donor with methylation catalyzed by PNMT. Early studies in rats and mice demonstrated that Epi is regulated in vivo by stress through genetic control of its biosynthesis by PNMT (reviewed in Kvetnansky et al 2009;Wong et al 2010). In the rat adrenal medulla, IMMO stress increases both PNMT mRNA and protein expression with similar patterns and extent of change (Tai et al 2007;Viskupic et al 1994;Wong et al 2002Wong et al , 2004Wong et al , 2008.…”
Section: Epi Regulation By Stressmentioning
confidence: 99%
See 4 more Smart Citations
“…S-adenosylmethionine is the methyl donor with methylation catalyzed by PNMT. Early studies in rats and mice demonstrated that Epi is regulated in vivo by stress through genetic control of its biosynthesis by PNMT (reviewed in Kvetnansky et al 2009;Wong et al 2010). In the rat adrenal medulla, IMMO stress increases both PNMT mRNA and protein expression with similar patterns and extent of change (Tai et al 2007;Viskupic et al 1994;Wong et al 2002Wong et al , 2004Wong et al , 2008.…”
Section: Epi Regulation By Stressmentioning
confidence: 99%
“…Research in rats indicates that critical transcriptional activators of PNMT (see Wong et al 2010, for review) include early growth response gene-1 (Egr-1), specificity protein 1 (Sp1), glucocorticoid receptor (GR), glial cell missing-like factor (GCM l ), activating protein 2 (AP-2), and cMyc-activating factor (MAZ) with response elements (REs) for all residing within the proximal -893 bp of the gene promoter sequence upstream of the site of transcription initiation (?1, Fig. 3) (Ebert et al 1994Ebert and Wong 1995;Her et al 1999Her et al , 2003Ross et al 1990;Tai et al 2002;Tai and Wong 2003;Wong et al 1998).…”
Section: Epi Regulation By Stressmentioning
confidence: 99%
See 3 more Smart Citations